Effect of various extracts of Tabernaemontana divaricata on haloperidol induced catalepsy in rats (International Current Pharmaceutical Journal, 2014)
Parkinsons disease (PD) is one of the neurodegenerative diseases with selective loss of dopamine neurons of the substantia nigra pars compacta. In the present study, anti-cataleptic activity of Tabernaemontana divaricata leaves extracts viz. aqueous and ethanolic at different doses (50, 100 and 150 mg/kg i.p.) were studied using haloperidol (1 mg/kg, i.p.) induced catalepsy in rats which is a useful animal model for screening drugs for Parkinsons disease. Both the extracts were found to reduce catalepsy significantly (P